Inhibition of myeloperoxidase at the peak of experimental autoimmune encephalomyelitis restores blood–brain barrier integrity and ameliorates disease severity. Issue 4 (30th November 2015) - Zhang, Hao; Ray, Avijit; Miller, Nichole M.; Hartwig, Danielle; Pritchard, Kirkwood A.; Dittel, Bonnie N.
Abstract: Oxidative stress is thought to contribute to disease pathogenesis in the central nervous system (CNS) disease multiple sclerosis (MS). Myeloperoxidase (MPO), a potent peroxidase that generates toxic radicals and oxidants, is increased in the CNS during MS. However, the exact mechanism whereby MPO drives MS pathology is not known. We addressed this question by inhibiting MPO in mice with experimental autoimmune encephalomyelitis (EAE) using our non‐toxic MPO inhibitor N‐acetyl lysyltyrosylcysteine amide (KYC). We found that therapeutic administration of KYC for 5 days starting at the peak of disease significantly attenuated EAE disease severity, reduced myeloid cell numbers and permeability of the blood–brain barrier. These data indicate that inhibition of MPO by KYC restores blood–brain barrier integrity thereby limiting migration of myeloid cells into the CNS that drive EAE pathogenesis. In addition, these observations indicate that KYC may be an effective therapeutic agent for the treatment of MS. We propose that during experimental autoimmune encephalomyelitis (EAE) onset macrophages and neutrophils migrate into the CNS and upon activation release myeloperoxidase (MPO) that promotes disruption of the blood–brain barrier (BBB) and disease progression. KYC restores BBB function by inhibiting MPO activity and in so doing ameliorates disease progression. Abstract : We propose that during experimental autoimmune encephalomyelitis (EAE) onset macrophages and neutrophils migrate into the CNS and upon activation release myeloperoxidase (MPO) that promotes disruption of the blood–brain barrier (BBB) and disease progression. KYC restores BBB function by inhibiting MPO activity and in so doing ameliorates disease progression.